The Influence of Educational Background, Length of Business and Business Size on the Quality of Financial Reports of MSMEs in Medan Petisah District - Wiwik Apriani; Dwi Saraswati; Rahima Br Purba (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the influence of educational background, business duration, and business size on the quality of financial reports among Micro, Small, and Medium Enterprises (MSMEs) in Medan Petisah District. The research employs an associative design with a quantitative approach. The study population consists of 30 MSMEs, all of which were included as samples using a saturated sampling technique. Data were collected through questionnaires distributed to MSME owners or managers and analyzed using multiple linear regression with the aid of the SPSS program. The findings reveal that educational background and business duration do not have a significant effect on the quality of financial reports, while business size has a significant but negative influence. Taken together, these three variables significantly affect the quality of MSME financial reports. This suggests that improving the quality of MSME financial reporting requires a balance of knowledge, experience, and sufficient operational capacity.